The structure of developing semantic networks: Evidence from single and multiple nominal word associations in young monolingual and bilingual readers. (14th September 2020) - Spätgens, Tessa; Schoonen, Rob
ABSTRACT: The present study focuses on the effect of an important methodological choice in word association studies in children: the elicitation of single versus multiple responses. This choice has been shown to affect the numbers and types of associations adults produce, however, little is known about how it affects children's word associations. A total of 11, 725 associations to 80 nouns from 207 monolingual and bilingual minority children were classified according to a detailed coding system, and differences between the semantic characteristics of first, second, and third responses were examined. We show that in children as well, the multiple association task elicits more and qualitatively different responses, resulting in more diversified semantic networks surrounding the stimulus nouns. On the speaker level, reading comprehension scores were related differently to initial and later responses, suggesting a more complex measure of semantic knowledge emerges from the multiple word association task. No differences were found between monolingual and bilingual children's associative preferences. We argue that the multiple association task produces more detailed data on language users' semantic networks than the single association task, and suggest a number of ways in which this task could be employed in future research.